Presence and transcriptional activity of anaerobic fungi in agricultural biogas plants. (July 2017) - Dollhofer, Veronika; Callaghan, Tony M.; Griffith, Gareth W.; Lebuhn, Michael; Bauer, Johann
Highlights: Specific study on occurrence of anaerobic fungi in agricultural biogas plants. Anaerobic fungal 18S DNA only detected in biogas plants operated with cattle manure. GH5 endoglucanase transcripts found only in 2 anaerobic fungi positive digesters. Anaerobic fungi are probably transferred to digesters via animal manure. Description of a novel Piromyces species isolated from a digester. Abstract: Bioaugmentation with anaerobic fungi (AF) is promising for improved biogas generation from lignocelluloses-rich substrates. However, before implementing AF into biogas processes it is necessary to investigate their natural occurrence, community structure and transcriptional activity in agricultural biogas plants. Thus, AF were detected with three specific PCR based methods: (i) Copies of their 18S genes were found in 7 of 10 biogas plants. (ii) Transcripts of a GH5 endoglucanase gene were present at low level in two digesters, indicating transcriptional cellulolytic activity of AF. (iii) Phylogeny of the AF-community was inferred with the 28S gene. A new Piromyces species was isolated from a PCR-positive digester. Evidence for AF was only found in biogas plants operated with high proportions of animal feces. Thus, AF were most likely transferred into digesters with animal derived substrates. Additionally, high process temperatures in combination with long retention times seemed to impede AF survival and activity.